2018
DOI: 10.1177/0014402918771543
|View full text |Cite
|
Sign up to set email alerts
|

Reading Comprehension and Co-Teaching Practices in Middle School English Language Arts Classrooms

Abstract: This study reports practices implemented in over 2,000 minutes by 16 middle school special education and general education co-teaching pairs in English language arts classes. We report the extent to which teachers integrated literacy activities that support reading comprehension, the co-teaching models used, and the frequency with which each teacher led instruction. We also report the types of grouping structures teachers used and the extent to which teachers interacted with students with disabilities. Finally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 51 publications
2
49
0
3
Order By: Relevance
“…Instead they tended to rely on models that required fewer instructional modifications, such as parallel teaching or one teach, one assist (e.g. Ashton 2010; Brendle, Lock, and Piazza 2017; Casale-Giannola 2012; Klein 2009; Shankland 2011; Strogilos and Avramidis 2016; Volonino 2009;Wexler et al 2018). The frequent use of the one teach, one assist model in co-teaching was often discussed in terms of an unequal distribution of responsibilities and authority.…”
Section: Forms Of Cooperationmentioning
confidence: 99%
“…Instead they tended to rely on models that required fewer instructional modifications, such as parallel teaching or one teach, one assist (e.g. Ashton 2010; Brendle, Lock, and Piazza 2017; Casale-Giannola 2012; Klein 2009; Shankland 2011; Strogilos and Avramidis 2016; Volonino 2009;Wexler et al 2018). The frequent use of the one teach, one assist model in co-teaching was often discussed in terms of an unequal distribution of responsibilities and authority.…”
Section: Forms Of Cooperationmentioning
confidence: 99%
“…More recently, McKenna et al (2019) did document comprehension strategy and comprehension monitoring instruction but observed little direct vocabulary or small-group instruction. When we look more broadly at reading practices for students with mild disabilities, similar sentiments have been described in observations of the classroom reading practices directed at students with learning disabilities, both at the elementary (Ciullo et al, 2019) and secondary (Wexler et al, 2018) school levels. The lack of observed research-based reading practices necessitates that teachers of students with EBD with co-occurring reading delays have ready access to professional resources to help them increase and improve implementation of research-based practices.…”
Section: Why Half Empty?mentioning
confidence: 63%
“…Special educators spent 45% of their time monitoring students. More recently, Wexler et al (2018) observed instruction for 16 coteaching pairs in grades 6–8 during English/Language Arts classes. They found that literacy instruction occurred for 31.2% of the observed time.…”
Section: Current Practicementioning
confidence: 99%